Organosilicon filler surface treating agent with asymmetric different ends, preparation method and application
The surface chemical modification of thermally conductive inorganic filler particles through the heretical asymmetric silicone filler surface treatment agent is solved, and the problem of insufficient thermal conductivity and filling amount in the prior art is achieved, and a silicone composite material with high thermal conductivity, excellent high temperature resistance and aging properties is realized.
Patent Information
- Application Number
- CN202311240217.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-25
- Publication Date
- 2025-03-25
AI Technical Summary
The prior art has limitations in improving the fill amount and thermal conductivity of thermally conductive inorganic fillers, and the commonly used small molecule silane coupling agent has limited effect on surface modification treatment, and the process is dangerous and cost-effective.
The surface treatment agent with a long chain single-ended alkoxy polysiloxane structure is prepared by a polymerization reaction of an organocyclic silicone monomer and an initiator, combined with the end capping reaction of chlorosilane and an acid binding agent, and a surface treatment agent with a long chain single-ended alkoxy polysiloxane structure is used to chemically modify the surface of the thermally conductive inorganic filler particles.
It realizes efficient surface modification of thermally conductive inorganic filler particles, improves the surface hydrophobicity and dispersion of filler particles, enhances the thermal conductivity, high temperature and aging resistance of the silicone composite material, and reduces the viscosity and storage stability of the material.
Smart Images

Figure CN119684606A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of organic silicon materials, and specifically relates to a heterodyne asymmetric organic silicon filler surface treatment agent and a preparation method thereof, as well as application in organic silicon thermal (electrical) conductive materials. Background Art
[0002] With the rapid development of 5G technology and new energy industries, the power density and integration of electronic components are getting higher and higher, and the heat generated during operation is increasing. If the heat cannot be dissipated in time, the life of the electronic components will be reduced and their working state will be affected. Efficient thermal management is an important issue that needs to be considered in the fields of electronic products, power batteries, high-power LED lighting, etc.
[0003] Thermal interface materials are widely used in the field of heat dissipation of electronic components. They can be filled between heat dissipation devices and electronic components to exclude air, reduce the contact thermal resistance caused by micro gaps and uneven holes between them, and enable the heat generated by electronic components to be more quickly transferred to the heat dissipation devices through the thermal interface materials, thereby reducing the operating temperature of electronic components and extending their service life. Among them, thermally conductive silicone composite materials are one of the hot spots in the research of thermal interface materials. They refer to thermally conductive compositions prepared by liquid polysiloxane composites with thermally conductive inorganic fillers such as aluminum oxide, aluminum hydroxide, zinc oxide, boron nitride, and aluminum powder. Silicone materials have been favored and widely used due to their outstanding advantages in high and low temperature resistance, insulation, softness, low stress, and cost.
[0004] Generally speaking, the higher the content of thermally conductive inorganic filler in polysiloxane, the greater the thermal conductivity of the thermally conductive silicone composite material. Due to the large difference in the physicochemical properties between polysiloxane and thermally conductive inorganic filler, in order to increase the filling amount of thermally conductive filler, it is necessary to perform surface chemical modification on the inorganic filler particles, thereby improving the compatibility and dispersibility between polysiloxane and inorganic filler, eliminating or reducing the phonon scattering caused by the polymer-filler interface, reducing the interfacial thermal resistance of the system, and improving the thermal conductivity of the material.
[0005] At present, there are many methods for surface modification of inorganic filler particles, and there are also many reports on the synthesis of surface treatment agents, but there are still many problems. Small molecule silane coupling agents are conventionally used to modify the surface of filler particles, such as vinyl trimethoxysilane, vinyl triethoxysilane, glycidyl ether propyl trimethoxysilane, long-chain alkyl alkoxysilane (C4-C18), etc. However, these small molecule silane coupling agents have weak binding force and poor coating on the surface of filler particles due to their short chain segments, and the treatment effect that can be achieved is very limited. It will also cause the storage of organic silicon composite materials to be "structured", and the unreacted small molecule silane coupling agents are difficult to completely remove, and they will be free in the system, causing the material to produce low-boiling substances during use, causing the risk of voids inside the thermal conductive material, thereby affecting the thermal conductivity and other properties of the material.
[0006] Existing patent document CN113024809A discloses a linear single-end trialkoxysilane-terminated polysiloxane fluid, which adopts a preparation method of non-equilibrium anionic ring-opening polymerization catalyzed by n-butyl lithium. The surface treatment agent obtained by this method has a precise and regular structure and a narrow molecular weight distribution. However, the preparation method has harsh conditions and uses n-butyl lithium, which is easily self-igniting in the air, as an initiator. The synthesis process is extremely dangerous.
[0007] CN115216011A discloses a method for preparing an iso-alkoxy silicone oil, and uses it to treat the surface of fillers and improve the compatibility between fillers and organic materials or organosilicon materials. The synthesized surface treatment agent has a uniform and controllable structure and a narrow molecular weight distribution, but the synthesis reaction uses a corrosive and self-igniting organic sodium (potassium) salt as an initiator, the preparation process is dangerous, and the synthesized alkoxy silicone oil has only one methoxy (or ethoxy) terminal in its structure, and its reaction activity is low when treating fillers, and the treatment effect is limited.
[0008] CN111333846A and CN111349243A disclose a method for preparing a single-end alkoxy and single-end methyl (or vinyl) polysiloxane, wherein the synthesis conditions require the use of a phosphazene catalyst, ammonia and dangerous and flammable aluminum isopropoxide, the reaction steps are numerous, and the synthesis process is complex, dangerous, not environmentally friendly and has a high cost.
[0009] In view of this, it is very necessary and of great research and development significance to realize the safe and environmentally friendly large-scale production of silicone filler surface treatment agents with excellent surface modification performance, so as to obtain silicone thermal conductive composite materials with high thermal conductivity, excellent high temperature resistance, aging resistance and storage stability. Summary of the invention
[0010] The present invention aims to solve the above-mentioned technical problems and provides a heresy asymmetric organosilicon filler surface treatment agent, preparation method and application. The filler treatment agent of the present invention has a precise molecular chain structure and the double-end active groups are easy to control. When applied to thermally conductive (electrically conductive) organosilicon materials, it can realize the surface chemical grafting modification treatment of inorganic filler particles, improve the surface hydrophobicity of filler particles, improve the compatibility between inorganic fillers and organosilicon polymers, improve the dispersibility and filling amount of inorganic fillers in polymers, improve the thermal (electrically conductive) performance of organosilicon composite materials, and reduce the viscosity of composite materials. At the same time, the preparation process of the organosilicon filler surface treatment agent of the present invention is simple, and it can be prepared by "one pot method". The process is safe and environmentally friendly, and it is suitable for industrial large-scale preparation and production.
[0011] The purpose of the present invention is achieved through the following technical solutions:
[0012] A heterodyne asymmetric organic silicon filler surface treatment agent, the treatment agent has a structure as shown in formula (I):
[0013]
[0014] In the above formula (I),
[0015] R1 is
[0016] One of;
[0017] R2 is phenyl or trifluoropropyl;
[0018] R3 is one of methyl, methoxy and ethoxy;
[0019] R4 is methyl or ethyl;
[0020] R5 is one of methyl, methoxy and ethoxy;
[0021] In formula (I), m=10-150, n=0-50, and p=0-50 are integers.
[0022] The present invention discloses a method for preparing a heterodyne asymmetric organic silicon filler surface treatment agent, comprising the following steps:
[0023] A. Add the mixed solution of organic cyclic siloxane monomer and initiator into the reaction kettle, then add the organic base solution, and stir the polymerization reaction at room temperature for 1 to 6 hours;
[0024] B. Add chlorosilane and acid binding agent to the system after polymerization in step A to carry out end-capping reaction, continue stirring for 1 to 20 hours, then remove the residue and filter to obtain a heteroterminal asymmetric organosilicon filler surface treatment agent, which has a structure shown in formula (I).
[0025] In the above step A of the technical solution of the present invention:
[0026] The organic cyclic siloxane monomer is selected from one or more of hexamethylcyclotrisiloxane, hexaphenylcyclotrisiloxane, 2,4,6-trimethyl-2,4,6-triphenylcyclotrisiloxane, and 2,4,6-trimethyl-2,4,6-tri(3,3,3-trifluoropropyl)cyclotrisiloxane;
[0027] The initiator is selected from any one of the following substances:
[0028] The solvent of the mixed solution of the organic cyclic siloxane monomer and the initiator is one or more of toluene, ether, tetrahydrofuran, cyclohexane, dichloromethane and anisole; the mass concentration of the mixed solution of the organic cyclic siloxane monomer and the initiator is 1-4 g / mL.
[0029] The organic base is selected from any one of the following substances:
[0030] The solvent of the organic alkali solution is one of tetrahydrofuran, toluene and dichloromethane; the mass concentration of the organic alkali solution is 0.1 g / mL.
[0031] Furthermore, in step A, the molar ratio of the organic cyclic siloxane monomer to the initiator is 3:1 to 70:1, and the molecular weight of the polysiloxane can be regulated by controlling the molar ratio of the monomer to the initiator; the molar ratio of the initiator to the organic base as a catalyst is 5:1 to 50:1, and the amount of catalyst added can affect the rate of the ring-opening polymerization reaction.
[0032] In the above step B of the technical solution of the present invention:
[0033] The chlorosilane is selected from any one of the following substances:
[0034] The acid binding agent is selected from one or more of triethylamine, pyridine and N,N-diisopropylethylamine.
[0035] Further, in step B,
[0036] The molar ratio of chlorosilane to initiator is 1.5:1 to 4:1. If the ratio is lower than this, the chlorosilane end-capping will be incomplete, that is, the end-capping cannot be completely converted into methoxy functional groups; if the ratio is higher than this, more chlorosilane substances will remain in the system, which will affect the purity of the obtained organosilicon filler surface treatment agent.
[0037] The molar ratio of the acid-binding agent to the initiator is 1.5:1 to 4.2:1. The acid-binding agent is used to react with the HCl produced after the chlorosilane is capped, and its amount corresponds to the amount of chlorosilane used. If the ratio is lower than this, the chlorosilane capping will be incomplete; if the ratio is higher than this, there will be more acid-binding agent remaining, which will cause trouble for separation and purification.
[0038] In the technical solution of the present invention, the reactions in step A and step B are carried out under an inert atmosphere, and the inert atmosphere is selected from a nitrogen atmosphere or an argon atmosphere.
[0039] The asymmetric organic silicon filler surface treatment agent having the structure shown in formula (I) of the present invention is applied to the preparation of heat-conductive organic silicon thermal interface material products, which can achieve surface chemical modification of heat-conductive (conductive) inorganic filler particles, improve the surface hydrophobicity of the filler particles, and obtain heat-conductive (conductive) organic silicon composite materials. The filler includes but is not limited to the following inorganic fillers: aluminum oxide, zinc oxide, aluminum hydroxide, magnesium oxide, silicon dioxide, silicon carbide, silicon nitride, aluminum nitride, boron nitride, gold, silver, aluminum, nickel, copper, zinc, carbon fiber, graphite, graphene and carbon nanotubes, diamond; the organic silicon filler surface treatment agent is 0.1-3.5% of the total weight of the filler.
[0040] Compared with the prior art, the present invention has the following beneficial effects:
[0041] 1. The organosilicon filler surface treatment agent of the present invention is prepared by a "one-pot" reaction using commercial bulk raw material cyclosiloxane as the initial raw material. Compared with the existing patents CN111333846A and CN111349243A which require multiple steps of reaction to synthesize the surface treatment agent, the present invention is faster and more efficient.
[0042] 2. The organic silicon filler surface treatment agent of the present invention is prepared by using commercial organic base as catalyst and silanol as initiator. Compared with the existing patents CN113024809A and CN115216011A which use dangerous organic lithium (sodium or potassium) salt as initiator, the present invention is safer and more reliable, and the reaction conditions are mild. Moreover, the post-reaction treatment is simple and easy to purify. A high-purity surface treatment agent can be obtained by simply removing the low concentration and filtering.
[0043] 3. The present invention adopts organic base-catalyzed non-equilibrium ring-opening polymerization to prepare the surface treatment agent, the molecular weight of which can be precisely controlled between 900-19000, the molecular weight distribution is narrow (PDI≤1.20), and the product structure is uniform and controllable.
[0044] 4. The terminal groups of the organic silicon filler surface treatment agent prepared by the present invention can be regulated by a silanol initiator, and the selectivity is wide. The terminal groups can be inert methyl groups, or active vinyl groups or silicon hydrogen groups. The vinyl or silicon hydrogen active groups can undergo silylation with hydrogen-containing silicone oil or vinyl silicone oil in the continuous phase during the curing process of the thermally conductive organic silicon material to form a cross-linked grid structure, which can give the material higher mechanical strength. Therefore, the surface treatment agent has a wide range of applications and can be used for single / double-component, various hardness, mechanical strength and thermal conductivity of thermally conductive gels, thermally conductive potting glue, thermally conductive silicone grease and thermally conductive gaskets and other products.
[0045] 5. When the organic silicon filler surface treatment agent prepared by the present invention is used in a thermally conductive (electrically conductive) organic silicon composite material, it can achieve surface chemical modification of the thermally conductive (electrically conductive) inorganic filler particles. By virtue of the long-chain single-end alkoxy polysiloxane structure of the surface treatment agent, the alkoxy group at one end of the polymer molecular chain reacts chemically with the hydroxyl group on the surface of the filler particle, and the long-chain polymer is grafted onto the surface of the inorganic filler particle. The polymer will cover the filler particle, so it has an excellent filler surface treatment effect, can significantly improve the surface hydrophobicity of the inorganic filler particles, improve the compatibility between the inorganic filler and the organic silicon polymer, improve the dispersibility and filling amount of the inorganic filler in the polymer, reduce the phonon scattering at the polymer-filler interface, reduce the interfacial thermal resistance of the system, improve the thermal conductivity of the material, and reduce the viscosity of the entire composite material, thereby preparing an organic silicon thermal conductive composite material with high thermal conductivity, excellent high temperature resistance, aging resistance and storage stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1 The H NMR spectra of the organic silicon filler surface treatment agents 1 to 3 prepared in Examples 1 to 3 of the present invention are ( 1 H NMR) curve,
[0047] Among them, curve a represents treatment agent 1, curve b represents treatment agent 2, and curve c represents treatment agent 3. DETAILED DESCRIPTION
[0048] In order to better explain the present invention, the present invention is specifically described below in conjunction with embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by technicians in this field based on the contents of the present invention still belong to the scope of protection of the present invention.
[0049] Example 1
[0050] 500g (2.25mol) hexamethylcyclotrisiloxane, 10.125g (112.50mmol) initiator and 255mL toluene were added to a three-necked flask, and nitrogen was blown into the system while the raw monomers were dissolved. A tetrahydrofuran solution of an organic base (0.1g / mL, 7.83mL, 5.625mmol) was then added to the three-necked flask, and the polymerization reaction was stirred at room temperature for 2h. Then, chlorosilane (35.24g, 225mmol) and triethylamine (23.91g, 236.25mmol) as an acid binding agent were added to the reaction system for end-capping reaction, and stirring was continued at room temperature for 12h. After the reaction was completed, the reaction mixture was concentrated under reduced pressure (-0.085MPa to -0.1MPa) to remove low-boiling substances such as solvents, and then filtered to remove insoluble salts to obtain 495g of a clear and transparent oily liquid (yield 94%), which was an organic silicon filler surface treatment agent 1, and its structural formula is as follows:
[0051]
[0052] Among the above components,
[0053] The initiator is
[0054] Organic base is
[0055] Chlorosilane is
[0056] The number average molecular weight is 4550 and the polydispersity index PDI is 1.14 as tested by GPC (gel permeation chromatography). It also has the following NMR characterization data: 1 H NMR (400MHz, CDCl3), δ (ppm): 3.57(-Si-OC H 3), 0.24~-0.12(C H 3-Si-C H 3, (C H 3)3-Si-). H NMR spectrum of silicone filler surface treatment agent 1 ( 1 H NMR) curves are as follows Figure 1 As shown in curve a in the figure, there is an obvious methoxy characteristic peak at 3.57 ppm, indicating that the silicone filler surface treatment agent 1 was successfully prepared through ring-opening polymerization and end-capping reaction.
[0057] Example 2
[0058] 500g (2.25mol) hexamethylcyclotrisiloxane, 11.50g (112.50mmol) initiator and 255mL toluene were added to a three-necked flask, and nitrogen was blown into the system while the raw monomers were dissolved. A toluene solution of an organic base (0.1g / mL, 7.83mL, 5.625mmol) was then added to the three-necked flask, and the polymerization reaction was stirred at room temperature for 2.5h. Then, chlorosilane (35.24g, 225mmol) and triethylamine (23.91g, 236.25mmol) as an acid binding agent were added to the reaction system for end-capping reaction, and stirring was continued at room temperature for 12h. After the reaction was completed, the reaction mixture was concentrated under reduced pressure (-0.085MPa to -0.1MPa) to remove low-boiling substances such as solvents, and then filtered to remove insoluble salts to obtain 496g of a clear and transparent oily liquid (yield 94%), which was an organic silicon filler surface treatment agent 2, and its structural formula is as follows:
[0059]
[0060] Among the above components,
[0061] The initiator is
[0062] Organic base is
[0063] Chlorosilane is
[0064] The number average molecular weight is 4600 and the polydispersity index PDI is 1.13 as tested by GPC (gel permeation chromatography). It also has the following NMR characterization data: 1 H NMR (400MHz, CDCl3), δ (ppm): 6.25~5.62(-Si-C H =C H 2), 3.57(-Si-OC H 3), 0.27~-0.12(C H 3-Si-C H 3). H NMR spectrum of silicone filler surface treatment agent 2 ( 1 H NMR) curves are as follows Figure 1 As shown in curve b, there are obvious vinyl characteristic peaks at 6.25-5.62 ppm and obvious methoxy characteristic peaks at 3.57 ppm, indicating that the silicone filler surface treatment agent 2 was successfully prepared by ring-opening polymerization and end-capping reaction.
[0065] Example 3
[0066] 500g (2.25mol) hexamethylcyclotrisiloxane, 16.91g (112.50mmol) initiator and 255mL toluene were added to a three-necked flask, and nitrogen was blown into the system while the raw monomers were dissolved. A toluene solution of an organic base (0.1g / mL, 7.83mL, 5.625mmol) was then added to the three-necked flask, and the polymerization reaction was stirred at room temperature for 2.5h. Then, chlorosilane (35.24g, 225mmol) and triethylamine (23.91g, 236.25mmol) as an acid binding agent were added to the reaction system for end-capping reaction, and stirring was continued at room temperature for 12h. After the reaction was completed, the reaction mixture was concentrated under reduced pressure (-0.085MPa to -0.1MPa) to remove low-boiling substances such as solvents, and then filtered to remove insoluble salts to obtain 501g of a clear and transparent oily liquid (yield 94%), which was an organic silicon filler surface treatment agent 3, and its structural formula is as follows:
[0067]
[0068] Among the above components,
[0069] The initiator is
[0070] Organic base is
[0071] Chlorosilane is
[0072] The number average molecular weight is 4610 and the polydispersity index PDI is 1.13 as tested by GPC (gel permeation chromatography). It also has the following NMR characterization data: 1 H NMR (400MHz, CDCl3), δ (ppm): 4.70 (-Si- H ), 3.57(-Si-OC H 3), 0.26~-0.12(C H 3-Si-C H 3). H NMR spectrum of silicone filler surface treatment agent 3 ( 1 H NMR) curves are as follows Figure 1 As shown in curve c in FIG, there is an obvious Si-H characteristic peak at 4.70 ppm and an obvious methoxy characteristic peak at 3.57 ppm, indicating that the silicone filler surface treatment agent 3 was successfully prepared by ring-opening polymerization and end-capping reaction.
[0073] Example 4
[0074] 500g (2.25mol) hexamethylcyclotrisiloxane, 64.40g (270mmol) initiator and 188mL tetrahydrofuran were added to a three-necked flask, and nitrogen was blown into the system while the raw monomers were dissolved. A tetrahydrofuran solution of an organic base (0.1g / mL, 8.27mL, 5.4mmol) was then added to the three-necked flask, and the polymerization reaction was stirred at room temperature for 6h. Then, chlorosilane (160.96g, 810mmol) and pyridine (67.27g, 850.5mmol) as an acid binding agent were added to the reaction system for end-capping reaction, and stirring was continued at room temperature for 5h. After the reaction was completed, the reaction mixture was concentrated under reduced pressure (-0.085MPa to -0.1MPa) to remove low-boiling substances such as solvents, and then filtered to remove insoluble salts to obtain 568g of a clear and transparent oily liquid (yield 92%), which was an organic silicon filler surface treatment agent 4, and its structural formula is as follows:
[0075]
[0076] Among the above components,
[0077] The initiator is
[0078] Organic base is
[0079] Chlorosilane is
[0080] The number average molecular weight is 2060 and the polydispersity index PDI is 1.17 as tested by GPC (gel permeation chromatography). It also has the following NMR characterization data: 1 H NMR (400MHz, CDCl3), δ (ppm): 3.84(-Si-OC H 2CH3), 1.22(-Si-OCH2C H 3), 0.22~-0.12(C H 3-Si-C H 3. C H 3-Si-, (C H 3)3-Si-).
[0081] Example 5
[0082] 384.86g (1.73mol) hexamethylcyclotrisiloxane, 212.51g (0.52mol) 2,4,6-trimethyl-2,4,6-triphenylcyclotrisiloxane, 15.81g (103.83mmol) initiator and 149mL toluene were added to a three-necked flask, and nitrogen was blown into the system while the raw monomers were dissolved. A toluene solution of an organic base (0.1g / mL, 5.27mL, 3.46mmol) was then added to the three-necked flask, and the polymerization reaction was stirred at room temperature for 4h. Then, chlorosilane (36.51g, 259.58mmol) and N,N-diisopropylethylamine (35.23g, 272.55mmol) as an acid binding agent were added to the reaction system for end-capping reaction, and stirring was continued at room temperature for 16h. After the reaction was completed, the reaction mixture was concentrated under reduced pressure (-0.085 MPa to -0.1 MPa) to remove the solvent and other low-boiling substances, and then filtered to remove the insoluble salt to obtain 584 g of a clear and transparent oily liquid random copolymer (yield 93%), which was the silicone filler surface treatment agent 5, and its structural formula is as follows:
[0083]
[0084] Among the above components,
[0085] The initiator is
[0086] Organic base is
[0087] Chlorosilane is
[0088] The number average molecular weight is 6010 and the polydispersity index PDI is 1.12 as tested by GPC (gel permeation chromatography). It also has the following NMR characterization data: 1 H NMR (400MHz, CDCl3), δ (ppm): 7.32-7.11(-Si- Ph ), 3.57(-Si-OC H 3), 0.63~-0.12((C H 3) 2Ph-Si-, C H 3-Si-Ph, C H 3-Si-C H 3).
[0089] Example 6
[0090] 291.42g (1.31mol) hexamethylcyclotrisiloxane, 214.16g (0.36mol) hexaphenylcyclotrisiloxane, 237.03g (0.58mol) 2,4,6-trimethyl-2,4,6-triphenylcyclotrisiloxane, 9.33g (43.55mmol) initiator and 185mL anisole were added to a three-necked flask, and nitrogen was blown into the system while the raw monomers were dissolved. A dichloromethane solution of an organic base (0.1g / mL, 5.41mL, 4.355mmol) was added to the three-necked flask, and the polymerization reaction was stirred at room temperature for 3h. Then, chlorosilane (27.29g, 174.2mmol) and triethylamine (18.51g, 182.91mmol) as an acid binding agent were added to the reaction system for end-capping reaction, and stirring was continued at room temperature for 20h. After the reaction, the reaction mixture was concentrated under reduced pressure (-0.085 MPa to -0.1 MPa) to remove the solvent and other low-boiling substances, and then filtered to remove the insoluble salt to obtain 698 g of a clear and transparent oily liquid random copolymer (yield 92%), which is the silicone filler surface treatment agent 6, and its structural formula is as follows:
[0091]
[0092] Among the above components,
[0093] The initiator is
[0094] Organic base is
[0095] Chlorosilane is
[0096] The number average molecular weight is 18060 and the polydispersity index PDI is 1.13 as tested by GPC (gel permeation chromatography). It also has the following NMR characterization data: 1 H NMR (400MHz, CDCl3), δ (ppm): 7.61-7.10(-Si- Ph ), 3.57(-Si-OC H 3), 0.66~-0.12(C H 3(Ph)2-Si-,C H 3-Si-Ph, C H 3-Si-C H 3).
[0097] Example 7
[0098] 500g (2.25mol) hexamethylcyclotrisiloxane, 7.21g (45mmol) initiator and 203mL cyclohexane were added to a three-necked flask, and nitrogen was blown into the system while the raw monomers were dissolved. A dichloromethane solution of an organic base (0.1g / mL, 30.55mL, 9mmol) was then added to the three-necked flask, and the polymerization reaction was stirred at room temperature for 1h. Then, chlorosilane (28.19g, 180mmol) and triethylamine (19.12g, 189mmol) as an acid binding agent were added to the reaction system for end-capping reaction, and stirring was continued at room temperature for 20h. After the reaction was completed, the reaction mixture was concentrated under reduced pressure (-0.085MPa to -0.1MPa) to remove low-boiling substances such as solvents, and then filtered to remove insoluble salts to obtain 488g of a clear and transparent oily liquid (yield 95%), which was an organosilicon filler surface treatment agent 7, and its structural formula is as follows:
[0099]
[0100] Among the above components,
[0101] The initiator is
[0102] Organic base is
[0103] Chlorosilane is
[0104] The number average molecular weight of the product was 11,000 and the polydispersity index (PDI) was 1.15 as tested by GPC (gel permeation chromatography). The product also has the following NMR characterization data: 1 H NMR (400MHz, CDCl3), δ (ppm): 6.51~5.73 (C H 2=C H C(=O)-), 3.57(-Si-OC H 3), 3.49(-OC H 2-Si-), 0.27~-0.12(C H 3-Si-C H 3).
[0105] The asymmetric organic silicon filler surface treatment agent having the structure shown in formula (I) prepared by the present invention is applied to the preparation of thermally conductive organic silicon thermal interface material products, so as to achieve surface chemical modification of thermally conductive (conductive) inorganic filler particles, improve the surface hydrophobicity of the filler particles, and obtain a thermally conductive (conductive) organic silicon composite material.
[0106] The organic silicon filler surface treatment agents prepared in Examples 1-3 are selected below and used to prepare organic silicon thermal conductive potting adhesive materials.
[0107] Example 8
[0108] 300 parts of spherical alumina with a median particle size (D50) of 30 μm, 200 parts of spherical alumina with a median particle size (D50) of 10 μm, 100 parts of spherical alumina with a median particle size (D50) of 2 μm, 100 parts of aluminum hydroxide with a median particle size (D50) of 1 μm, 54 parts of double-ended vinyl polydimethylsiloxane with a viscosity of 150 mPa·s and 4 parts of the silicone filler surface treatment agent 1 prepared in Example 1 are added to a kneader, kneaded at room temperature for 3 h, then heated to 110°C, vacuum kneaded for 1 h, the vacuum degree was -0.08 MPa, and then cooled to room temperature and filled with nitrogen to break the vacuum to obtain base glue 1. The kneaded base glue 1 is divided into two parts and placed in planetary mixers A and B. In planetary mixer A, 17 parts of double-terminal vinyl polydimethylsiloxane with a viscosity of 150 mPa·s, 3 parts of color paste and 1 part of catalyst (platinum-vinylsiloxane complex with an effective content of platinum atoms of 5000 ppm) are added in sequence to dilute into component A; in planetary mixer B, 7 parts of double-terminal vinyl polydimethylsiloxane with a viscosity of 150 mPa·s, 10 parts of double-terminal hydrogen-containing polydimethylsiloxane with a viscosity of 160 mPa·s, 3 parts of side hydrogen-containing polydimethylsiloxane with a hydrogen content of 0.3 wt% and 1 part of 1-ethynyl cyclohexanol inhibitor are added in sequence to dilute into component B. Planetary mixers A and B are stirred and mixed at room temperature for 30 minutes respectively, and then degassed, and the two-component silicone thermal conductive potting glue material 1 is obtained.
[0109] Example 9
[0110] 500 parts of spherical alumina with a median particle size (D50) of 50 μm, 300 parts of spherical alumina with a median particle size (D50) of 10 μm, 300 parts of spherical alumina with a median particle size (D50) of 2 μm, 100 parts of aluminum hydroxide with a median particle size (D50) of 1 μm, 60 parts of double-ended vinyl polydimethylsiloxane with a viscosity of 150 mPa·s and 12 parts of the silicone filler surface treatment agent 2 prepared in Example 2 are added to a kneader, kneaded at room temperature for 3 h, then heated to 110°C, vacuum kneaded for 1 h, the vacuum degree was -0.08 MPa, and then cooled to room temperature and filled with nitrogen to break the vacuum to obtain base glue 2. Take the kneaded base glue 2 and divide it into two parts and place them in planetary mixers A and B. In planetary mixer A, add 10 parts of double-terminal vinyl polydimethylsiloxane with a viscosity of 150mPa·s, 3 parts of color paste and 1 part of catalyst (platinum-vinylsiloxane complex with an effective content of platinum atoms of 5000ppm) in sequence to dilute it into component A; in planetary mixer B, add 10.5 parts of double-terminal hydrogen-containing polydimethylsiloxane with a viscosity of 150mPa·s, 2.5 parts of side hydrogen-containing polydimethylsiloxane with a hydrogen content of 0.5wt% and 1 part of 1-ethynylcyclohexanol inhibitor in sequence to dilute it into component B. Planetary mixers A and B are stirred and mixed at room temperature for 30 minutes respectively, and then degassed, and the two-component silicone thermal conductive potting glue material 2 is obtained.
[0111] Example 10
[0112] 500 parts of spherical alumina with a median particle size (D50) of 50 μm, 300 parts of spherical alumina with a median particle size (D50) of 10 μm, 300 parts of spherical alumina with a median particle size (D50) of 2 μm, 100 parts of aluminum hydroxide with a median particle size (D50) of 1 μm, 60 parts of double-ended vinyl polydimethylsiloxane with a viscosity of 150 mPa·s and 12 parts of silicone filler surface treatment agent 3 prepared in Example 3 are added to a kneader, kneaded at room temperature for 3 h, then heated to 90°C, vacuum kneaded for 1 h, the vacuum degree was -0.09 MPa, and then cooled to room temperature and filled with nitrogen to break the vacuum to obtain base glue 3. The kneaded base glue 3 is divided into two parts and placed in planetary mixers A and B. In planetary mixer A, 7 parts of double-terminal vinyl polydimethylsiloxane with a viscosity of 150 mPa·s, 3 parts of side vinyl polydimethylsiloxane with a vinyl content of 9.1 wt%, 3 parts of color paste and 1 part of catalyst (platinum-vinylsiloxane complex with an effective content of platinum atoms of 5000 ppm) are added in sequence to dilute into component A; in planetary mixer B, 13 parts of double-terminal hydrogen-containing polydimethylsiloxane with a viscosity of 150 mPa·s and 1 part of 1-ethynyl cyclohexanol inhibitor are added in sequence to dilute into component B. Planetary mixers A and B are stirred and mixed at room temperature for 30 minutes respectively, and then degassed, and the two-component silicone thermal conductive potting glue material 3 is obtained.
[0113] Comparative Example 1
[0114] This comparative example is a comparison with Example 8, except that the organosilicon filler surface treatment agent 1 in Example 8 is replaced with octadecyltrimethoxysilane, and other conditions are the same as those in Example 8.
[0115] Comparative Example 2
[0116] This comparative example is a comparison with Example 9, except that the organosilicon filler surface treatment agent 2 in Example 9 is replaced by a mixture of octadecyltrimethoxysilane and vinyltrimethoxysilane (mass ratio is 60 / 1), and other conditions are the same as those in Example 9.
[0117] Comparative Example 3
[0118] This comparative example is a comparison with Example 10. The organic silicon filler surface treatment agent 3 in Example 10 is replaced by octadecyl trimethoxysilane and trimethoxysilane containing silicon hydrogen (the structural formula of trimethoxysilane containing silicon hydrogen is ) (mass ratio is 60 / 1), and other conditions are the same as in Example 10.
[0119] The two-component silicone thermally conductive potting materials obtained in the above-mentioned Examples 8 to 10 and Comparative Examples 1 to 3 were subjected to product performance tests.
[0120] 1. Viscosity test: The viscosity of the sample after A / B=1 / 1 mixing was tested using the GB / T 2794-2013 method.
[0121] 2. Hardness test: Mix the two-component silicone thermal conductive potting glue according to A / B=1 / 1, degas it, pour it into 6mm thick molds, bake it in a 100℃ oven for 30 minutes, then cool it to room temperature, take out the sample, and test it using the GB / T531.1-2008 method.
[0122] 3. Thermal conductivity test: Prepare test specimens according to the above method 2 and test using ASTM D5470 method.
[0123] 4. Performance test after heat aging: Prepare test specimens according to the above method 2, put them into an electric blast oven, heat age them at 150°C for 1000h, then take out the specimens and place them at room temperature for 24h; use GB / T531.1-2008 method to test the hardness, and use ASTM D5470 method to test the thermal conductivity.
[0124] The relevant performance results are shown in Table 1.
[0125] Table 1
[0126]
[0127]
[0128] It can be seen from the data in Table 1 that the two-component organic silicon thermal conductive potting material prepared by surface modification of the thermal conductive inorganic filler with the organic silicon filler surface treatment agent of the present invention is compared with the thermal conductive potting material prepared by the conventional technology using a silane coupling agent (such as octadecyltrimethoxysilane, octadecyltrimethoxysilane and vinyltrimethoxysilane, etc.). Specifically, compared with Comparative Example 1 in Example 8, compared with Comparative Example 2 in Example 9, and compared with Comparative Example 3 in Example 10, the organic silicon thermal conductive material obtained by the present invention not only has a lower viscosity and a higher thermal conductivity, but also has a lower change in hardness and thermal conductivity after thermal aging at 150° C. for 1000 h, indicating that the thermal conductive material has excellent heat aging resistance, which is attributed to the long-chain single-end alkoxy polymer structure of the organic silicon filler surface treatment agent. After the long-chain polymer is grafted with the filler particles, the long-chain polymer can well coat the thermal conductive filler particles. In addition, by changing the terminal structure (methyl, vinyl, silane) of the surface treatment agent of the silicone filler, thermally conductive potting adhesives with different hardness and strength can be obtained to suit different material application scenarios.
[0129] The embodiments described above are only preferred implementation modes of the present invention. The implementation modes of the present invention are not subject to any limitation of the embodiments described above. Therefore, any other modifications, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principle of the present invention should be regarded as equivalent replacement methods and are included in the protection scope of the technical solution of the present invention.
Claims
1. A heterogeneous asymmetric organic silicon filler surface treatment agent, characterized in that: The treating agent has a structure as shown in formula (I): In the above formula (I), R1 is One of; R2 is phenyl or trifluoropropyl; R3 is one of methyl, methoxy and ethoxy; R4 is methyl or ethyl; R5 is one of methyl, methoxy and ethoxy; In formula (I), m=10-150, n=0-50, and p=0-50 are integers.
2. A method for preparing a heterodyne asymmetric organosilicon filler surface treatment agent, characterized in that: The steps include: A. Add the mixed solution of organic cyclic siloxane monomer and initiator into the reaction kettle, then add the organic base solution, and stir the polymerization reaction at room temperature for 1 to 6 hours; B. Add chlorosilane and acid binding agent to the system after polymerization in step A to carry out end-capping reaction, continue stirring for 1 to 20 hours, then remove the residue and filter to obtain a heteroterminal asymmetric organosilicon filler surface treatment agent, which has a structure shown in formula (I).
3. The method for preparing a heterosymmetric organosilicon filler surface treatment agent according to claim 2, characterized in that: In step A: The organic cyclic siloxane monomer is selected from one or more of hexamethylcyclotrisiloxane, hexaphenylcyclotrisiloxane, 2,4,6-trimethyl-2,4,6-triphenylcyclotrisiloxane, and 2,4,6-trimethyl-2,4,6-tri(3,3,3-trifluoropropyl)cyclotrisiloxane; The initiator is selected from any one of the following substances:
4. The method for preparing a heterotactically asymmetric organosilicon filler surface treatment agent according to claim 2 or 3, characterized in that: The solvent of the mixed solution of the organic cyclic siloxane monomer and the initiator is one or more of toluene, ether, tetrahydrofuran, cyclohexane, dichloromethane and anisole; the mass concentration of the mixed solution of the organic cyclic siloxane monomer and the initiator is 1-4 g / mL.
5. The method for preparing a heterosymmetric organosilicon filler surface treatment agent according to claim 2, characterized in that: In step A, the organic base is selected from any one of the following substances: The solvent of the organic alkali solution is one of tetrahydrofuran, toluene and dichloromethane; the mass concentration of the organic alkali solution is 0.1 g / mL.
6. The method for preparing a heterosymmetric organosilicon filler surface treatment agent according to claim 2, characterized in that: In step A, the molar ratio of the organic cyclic siloxane monomer to the initiator is 3:1 to 70:1; and the molar ratio of the initiator to the organic base is 5:1 to 50:
1.
7. The method for preparing a heterotactically asymmetric organosilicon filler surface treatment agent according to claim 2, characterized in that: In step B: The chlorosilane is selected from any one of the following substances: The acid binding agent is selected from one or more of triethylamine, pyridine and N,N-diisopropylethylamine.
8. The method for preparing a heterosymmetric organosilicon filler surface treatment agent according to claim 2, characterized in that: The molar ratio of the chlorosilane in step B to the initiator in step A is 1.5:1 to 4:1; the molar ratio of the acid binding agent in step B to the initiator in step A is 1.5:1 to 4.2:
1.
9. The method for preparing a heterotactically asymmetric organosilicon filler surface treatment agent according to claim 2, characterized in that: The reactions in step A and step B are carried out under an inert atmosphere, and the inert atmosphere is selected from a nitrogen atmosphere or an argon atmosphere.
10. Using an asymmetric organic silicon filler surface treatment agent in the preparation of a thermally conductive organic silicon thermal interface material product, the asymmetric organic silicon filler surface treatment agent is the asymmetric organic silicon filler surface treatment agent having a structure as shown in formula (I) as described in claim 1, or the asymmetric organic silicon filler surface treatment agent having a structure as shown in formula (I) obtained by the preparation method described in any one of claims 2 to 9; the filler includes but is not limited to the following inorganic fillers: aluminum oxide, zinc oxide, aluminum hydroxide, magnesium oxide, silicon dioxide, silicon carbide, silicon nitride, aluminum nitride, boron nitride, gold, silver, aluminum, nickel, copper, zinc, carbon fiber, graphite, graphene and carbon nanotubes, diamond; the organic silicon filler surface treatment agent is 0.1 to 3.5% of the total weight of the filler.
Citation Information
Patent Citations
Preparation method of single-terminal alkoxy single-terminal methyl polydimethylsiloxane
CN111333846A
Preparation method of single-terminal alkoxy single-terminal vinyl polydimethylsiloxane
CN111349243A
Preparation method of single-ended trialkoxysiloxy terminated polysiloxane fluid
CN113024809A
Heterogeneous-end alkoxy silicone oil as well as preparation method and application thereof
CN115216011A
Cited By
Breakdown-resistant insulated power cable and preparation method thereof
CN121379022A
A puncture-resistant insulated power cable and a method for producing the same
CN121379022B